PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS VISUAL BASIC 6.0 PADA POKOK BAHASAN STRUKTUR ATOM UNTUK KELAS X SMA SEDERAJAT - Ryndie Suci Ramadhani; Rasmiwetti '; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Development of interactive learning media based on Visual Basic 6.0 on the topic Structure Atomic has been done. Development of interactive learning media to get a valid and practical. The research method used ADDIE models which consists of stages are Analisys, Design, Development, Implementation and Evaluation. Data collected technique used validation sheet was given to three validators (media experts and matter expert). The results showed score of the designing aspects was 93,52 %, pedagogic aspect 93,33%, the content aspect was 95,81 % and the ease of use aspect was 97,62%. Average score overall validation of interactive learning media based on Visual Basic 6.0 on the topic Struktured Atomic was 95,63%. A valid interactive learning media then trial used by practitioners (user) questionnaire responses of teacher was score 95,65 % with categories valid and can be use in learning process.